Tinjauan Fikih Mamalah terhadap Implementasi Jual Beli Akad Istishna’ di Konveksi X - Marjan Laraswati; Panji Adam Agus Putra; Ira Siti Rohmah Maulida (UNISBA Press, 2021)
Abastrac. In X convection, buying and selling orders for an item uses the concept of an istishna contract. Istishna' contract is a sale-purchase contract on an order for the manufacture of goods with certain criteria and conditions agreed upon between the consumer (buyer/mustashni') and the producer (maker/shani'). The existence of istishna' conditions that are not fulfilled in the sale and purchase transaction of ordering goods. In ordering goods, the specifications of the goods needed are not explained and the khiyar rights owned by consumers are ignored by the convection party. The author's purpose in this study is first to find out the sale and purchase transaction of istishna' contract in the X convection, secondly to find out the review of muamalah fiqh on the istishna' contract in the X convection. The research approach is using sociological juridical, the type of data using field research, data sources using primary and secondary data, data collection through observation, interviews, and documentation. The results in the first study are the occurrence of conditions that are not met as a result consumers are not satisfied with the results of the goods that have been produced and the khiyar rights owned by consumers are ignored by the convection party, the second is a review of Islamic law on the practice of buying and selling istishna contracts in convection Prees Collection's Terms in the istishna' contract there are still things that have not been fulfilled by the convection owner, the condition is that the goods that are the object of istishna' must be clear both in quantity and quality. The occurrence of discrepancies is included in the category of fasid contracts. Abstrak. Pada konveksi X jual-beli pesanan suatu barang menggunakan konsep akad istishna’. Akad istishna’ merupakan akad jual-beli pada pemesanan pembuatan barang dengan kriteria dan persyaratan tertentu yang disepakati antara konsumen (pembeli/mustashni’) dengan produsen (pembuat/shani’). Adanya syarat istishna’ yang tidak terpenuhi dalam transaksi jual-beli pemesanan barang. Pada pemesanan barang tidak dijelasakan spesifikasi barang yang dibutuhkan dan hak khiyar yang dimliki konsumen diabaikan oleh pihak konveksi. Tujuan penulis dalam penelitian ini adalah pertama untuk mengetahui transaksi jual beli akad istishna’ dikonveksi Press Collection, kedua untuk mengetahui tinjauan fikih muamalah terhadap akad istishna’ dikonveksi X. Pendekatan penelitian ini penulis menggunakan yuridis sosiologis, jenis data menggunakan field research, sumber data mengggunakan data primer dan data skunder, pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil dalam penelitian yang pertama faktor terjadinya syarat yang tidak terpenuhi akibatnya kosumen tidak merasa puas dengan hasil barang yang telah diproduksi dan hak khiyar yang dimiliki oleh konsumen diabaikan oleh pihak konveksi,kedua tinjauan hukum islam terhadap praktik jual-beli akad istishna’ dikonveksi Prees Collection’s Syarat dalam akad istishna’ masih ada yang belum terpenuhi oleh pemilik konveksi, syarat tersebut barang yang menjadi objek istishna’ harus jelas baik kuantitas maupun kualitas.Terjadinnya ketidak sesuaian termasuk kepada katagori akad yang fasid.